Introduction to communication (Schaumburg, IL. : |b, 2010)
This introductory research text trains students to gather research evidence, develop research arguments, and think critically about them. This textbook is ideal for the student with little or no research background. Fundamental research issues are discussed in detail and provide building blocks for further study, giving students both comfort and knowledge. This textbook is designed to teach students how to "do scholarship" by making reasoned cases and offering research conclusions
Keywords: Communication,Truyền thông; Research,Methodology,Nghiên cứu,Phương pháp